POTENSI ANTIOKSIDAN DAN SIFAT SITOTOKSIS EKSTRAK KULIT KAYU SEMBILAN JENIS TUMBUHAN DARI TAMAN NASIONAL LORE LINDU - Saefudin; Efrida Basri (Jurnal Penelitian Hasil Hutan, 2016)
Bark extracts of nine plant species from Lore Lindu National Park (NP) had been studied for the antioxidant potential and their cytotoxic effects. The antioxidant activity was tested by determining the peroxidevalue (POV) using the iodometric method. The toxicity test was done by counting the death of shrimp larva (Artemia salina) using Brine Schrimp Lethality Test (BSLT) method. The test results showed three bioactive components (saponin, flavonoid, and polyphenol) were mostly obtained fromthe 3 plant species that have low POV, namely Dysoxylum gaudichaudianum, Gardenia augusta, and Nauclea orientalis. The most striking of cytotoxic effects (LC50< 200 μg/ml) were found from Koordersiodendron pinnatum (170.86 μg/ml), Nauclea orientalis (182.89 μg/ml), and Kleinhovia hospita (191.35 μg/ml) extracts.